(untitled) (World Bulletin of Social Sciences, 2022)
The research aims to clarify the importance of adopting IAS (12) "income taxes" as a tool for measuring and disclosing income taxes in financial statements by comparing the calculation of income tax according to the standard in question and the calculation of tax according to Iraqi accounting rule No. 13.